Study of the genotoxicity of multi-walled carbon nanotubes in human cell lines from the airway epithelia: implications for the regulatory testing of nanomaterials - Louro, Henriqueta (2014)
Carbon nanotubes (CNTs) have been employed in energy appliances and electronics and are the most widely used organic materials for tissue engineering applications. One major concern for human health is the similarity, in size and shape, between multi-walled carbon nanotubes (MWCNTs) and asbestos fibers, which are recognized carcinogens to humans following long term exposure by inhalation. Although a number of recent studies have addressed the genotoxicity of MWCNTs, many contradictory results have been generated, probably related with variations in the NMs size, aspect ratio, surface properties, agglomeration state, bio persistence and dose, representing a challenge to the assessment of their potential hazards. Thus, it is presently not clear how to predict which type of CNTs are actually harmful to humans, posing a real problem to the regulation of CNTs during their life cycle. The present work aimed at studying the potential of standard genotoxicity assays to be used in MWCNTs hazard assessment, while giving insight into how various physical chemical parameters affect the end points analyzed in order to assess their toxicity in vitro, in cell lines representative of the airway epithelia. The genotoxicity and oxidative DNA damaging potential of four MWCNTs (NM-400, NM-401, NM-402 and NM-403, from JRC repository), essentially differing in length, aspect ratio and surface modifications, was tested by the micronucleus assay and by the comet and the FPG-modified comet assays using human-derived bronchial epithelial cells (BEAS-2B) and type-II alveolar cells (A549). The results showed that NM-402 and NM-403 exposure did not cause any genotoxicity or oxidative DNA damage in BEAS-2B cells. In contrast, their ability to cause DNA damage in A549 cells was distinct: NM-402 caused a dose-dependent induction of micronuclei while NM-403 was not genotoxic. The differences observed may be related with their different length and aspect ratio (both have similar diameter), being NM-402 the longest and displaying the highest aspect ratio. Thus, the result of the higher genotoxic potential of NM402 in A549 cells apparently supports the assumption that the length of the CNT might be critical to their toxic potential. Data on NM-400 and NM-401, that differ in length, diameter and coating is underway and will give more insight into the most relevant properties for toxicity evaluation. The overall data are also expected to further allow to compare and extrapolate genotoxicity results and to contribute to the identification of the most suitable metrics (e.g., size, aspect ratio, or coating) for hazard identification. Regarding safety assessment, the different genotoxicity observed for these two closely related MWCNTs highlights the importance of investigating the toxic potential of each NM individually, instead of considering a common effect related to high aspect ratio NMs.